Occurrence and distribution of a newly discovered peptide, galanin, in the mammalian enteric nervous system. Issue 7 (July 1986) - Bishop, A E; Polak, J M; Bauer, F E; Christofides, N D; Carlei, F; Bloom, S R
Abstract : Galanin, a newly discovered peptide, was found throughout the gastrointestinal tract of man, pig, and rat, exclusively in nerves. The concentrations of immunoreactive galanin ranged from 3.7 +/- 0.7 (mean +/- SEM) pmol/g in rat antrum to 76.5 +/- 14.3 pmol/g in pig colon. The predominantly intrinsic origin of the galanin nerves was shown by the finding of the peptide in submucosal ganglion cells, the majority of which also contained VIP. Furthermore, neither extrinsic denervation of the gut nor administration of capsaicin, which selectively destroys extrinsic afferent fibres, had any significant effect on the galanin innervation. The caudal projection of galanin-immunoreactive fibres was demonstrated by complete transection of the gut, which led to their reduction in the 1 to 2 cm distal to the cut. The abundance of galanin in the innervation of the mammalian gut and its reported action on smooth muscle contractility suggest this peptide to be a novel regulatory factor in the control of bowel function.